2014
DOI: 10.20491/isader.2014215950
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Worker Remittances on Economic Growth of Pakistan: Analysis of Pakistan s Economy

Abstract: We make this study for the purpose of getting logical answer about a very famous matter regarding contribution of worker's remittance in the growth of the economy of Pakistan. We also include different variables to evaluate the exact effect of foreign exchange earnings in economic growth of Pakistan by using time series data for the duration of 1991 to 2010. Here we applied OLS multiple regressions model and also check the assumptions of OLS by different diagnostic tests. The empirical and quantitative results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The results also do not agree with Shafqat et al (2014) found that there is a positive relationship between the worker's remittances of expatriate workers and economic growth in Pakistan, and does not agree with a study by Kratou & Gazdar (2014), found that there is a positive impact for worker's remittances on the economic growth in MENA countries for the long-term, also with Kundu et al (2012), found that there is a positive relationship between expatriate workers' remittances with the economic growth in Bangladesh that does not agree with the result of this research.…”
Section: Jordanian Migrant Worker's Remittances (Jmwr)mentioning
confidence: 84%
See 1 more Smart Citation
“…The results also do not agree with Shafqat et al (2014) found that there is a positive relationship between the worker's remittances of expatriate workers and economic growth in Pakistan, and does not agree with a study by Kratou & Gazdar (2014), found that there is a positive impact for worker's remittances on the economic growth in MENA countries for the long-term, also with Kundu et al (2012), found that there is a positive relationship between expatriate workers' remittances with the economic growth in Bangladesh that does not agree with the result of this research.…”
Section: Jordanian Migrant Worker's Remittances (Jmwr)mentioning
confidence: 84%
“…The results showed that there is a positive impact for foreign direct investment that effect on the local investment in 36 countries in the second period rather than the first period, also it helped these countries to improve their economy in the second period, due to the effectiveness of policies and initiatives adopted by the African Union, which contributed to increase the attraction of investment inside. A study by Shafqat et al (2014) investigated the impact of migrant workers remittances in the economic growth in Pakistan by using time series data from (1991 -2010). The dependent variable which used in the study is the natural log of GDP per capita (GROWTHi), and for the independent variables are; worker remittances that received to the country (WORREMi), ratio of money (FINDEVi), household consumption expenditure (CONSUMi), ratio of gross domestic savings (SAVINGi), and current account balance (CABALi) where this study analyzed the effect of the five independent variables and their impact on the dependent variable.…”
Section: Literature Review Conceptual Backgroundmentioning
confidence: 99%
“…Khathlan (2012) The results showed a positive and significant relationship between worker remittances and economic growth in both the long-run and the short-run. Shafqat et al(2014) The finding of the research indicated that foreign remittances are the famous mean of economic growth and have significant positive relationship with each other.…”
Section: Studymentioning
confidence: 92%
“…The review suggested that policy initiatives are essential to maximize the benefits of remittances. The analysis revealed that remittances had significant positive contribution to the economic growth of Pakistan (Qayyum et al, 2008;Shafqat et al, 2014).…”
Section: Review Of Literaturementioning
confidence: 98%